RISKS ASSOCIATED WITH ROBOTIC PROCESS AUTOMATION - HORVAT, Danijel; IVANIŠEVIĆ, Rajko; GLUŠČEVIĆ, Luka (Journal of process management and new technologies, 2024)
Background: Companies follow new trends to keep up with changes and find better ways of doing business. As one of the latest technologies, Robotic Process Automation (RPA) is in line with the automation trend that has become more prevalent in the 21st century. Since this technology is relatively new, many questions remain unanswered and have not been adequately addressed. Robotic process automation is under-researched in terms of risks that may arise during its development, implementation, or use. Purpose: The aim of this paper is to identify potential risks that may arise during the implementation of the Robotic Process Automation project. Research design/methodology/approach: Using Web of Science and SCOPUS index databases, a systematic review of the literature was conducted to answer the research question and achieve the defined goal. Results/conclusions: According to the results of the systematic literature review, Robotic Process Automation poses not only the typical risks associated with implementing any technology but also risks that are specific to this technology. Limitations/future research: Identified limitations refer to a small number of papers addressing the risks associated with robotic process automation. Furthermore, it is proposed that future research should include additional bases of studies.
Keywords: robotic process automation; risk management; risk assessment; risk